Efficacy and safety of sorafenib in very elderly patients aged 80 years and older with advanced hepatocellular carcinoma. Issue 13 (2nd April 2014) - Jo, Masayasu; Yasui, Kohichiroh; Kirishima, Toshihiko; Shima, Toshihide; Niimi, Toshihisa; Katayama, Takayuki; Mori, Takahiro; Funaki, Jun; Sumida, Yoshio; Fujii, Hideki; Takami, Shiro; Kimura, Hiroyuki; et al.
Abstract : Aim: Sorafenib is the standard systemic therapy for patients with advanced hepatocellular carcinoma (HCC). We aimed to assess the efficacy and safety of sorafenib therapy in very elderly patients aged 80 years and older with advanced HCC. Methods: In a retrospective multicenter study in Japan, we reviewed 185 patients (median age, 71 years; 82% male; 95% Child–Pugh class A) with advanced HCC who received sorafenib therapy. Data were compared between 24 (13%) patients aged 80 years and older and 161 (87%) patients aged less than 80 years. We used propensity score matching to adjust for differences between the two groups. Results: Median overall survival was 10.6 months in all patients: 11.7 months in patients aged 80 years and older and 10.5 months in those aged less than 80 years. There were no significant differences in overall survival, tumor response, and frequency and severity of drug‐related adverse events between patients aged 80 years and older and those aged less than 80 years in both the entire study cohort and the propensity‐matched cohort. Conclusion: Sorafenib may be effective and well tolerated, even in patients with advanced HCC who are aged 80 years and older, as well as those aged less than 80 years.